Overcoming the social stigma of consuming food waste by dining at the Open Table - Edwards, Ferne (My University, 2021)
Stigma is often encountered by recipients who receive food donations from charities, while the consumption of wasted food, also traditionally considered to be a stigmatized practice, has recently become part of a popular food rescue movement that seeks to reduce environmental impacts. These two stigmas—charitable donation and the consumption of waste—are brought together at the Open Table, a community group in Melbourne, Australia, that serves community meals cooked from surplus food. This paper examines how Open Table de-stigmatizes food donations through food waste discourse to enable greater social inclusion. I draw on the experiences of donors, cooks, volunteers and eaters gathered from diverse Open Table sites. Taking a ‘follow-the-thing’ approach, I analyze how food ‘waste’ becomes re-valued by embracing goals of environmental justice enacted through local processes of care and conviviality. Relying on networks of volunteers and not-for-profit agencies, Open Table provides a simple, effective and adaptable model for possible replication for overcoming drawbacks of traditional charity practices. Critically though, as hunger in society continues to grow, this approach is increasingly threatened by the need to ‘single out’ disadvantaged recipients to justify continued supply. This paper contributes to food poverty, waste, and Alternative Food Network literature in two important ways: first, by analyzing the outcomes of community food redistribution approaches with regards to stigma and inclusion; and secondly, by arguing that such holistic approaches need to be acknowledged, valued and supported to shift current discourses and practice.
Keywords: Food waste; Food donations; Social inclusion; Food poverty